2022
DOI: 10.3390/f13101624
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Juniperus macropoda Bossier Forest Ecosystem in Relation to Soil Physico-Chemical Characteristics in the Cold Desert of North-Western Himalaya

Abstract: Juniperus macropoda is the only tree species of a cold desert ecosystem that is experiencing high anthropogenic pressure and has a poor regeneration status due to harsh environmental conditions. Due to the limited distribution of Juniperus macropoda in this region, the species have remained largely unexplored in terms of understanding the distribution pattern along the elevation and soil fertility gradients. Therefore, the current research was carried out along the elevational gradient, starting from the base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…The diverse topography and elevation range in the mountainous forest ecosystem had a signi cant impact on the environmental microclimate (Qanbari, and Jamali, 2015), vegetation cover, and soil properties over a relatively short distance, frequently with sudden transitions (ecotone) in the vegetation sequences. The most important environmental elements that may contribute to the decline in growth and developmental features along an altitudinal gradient include temperature, light intensity, soil moisture, and fertility status in the alpine ecosystem (Kumar et al 2022b). Due to changes in abiotic variables such as climate, soil, and temperature as well as the altitudinal gradient, especially in undisturbed mountain ecosystems, the altitudinal gradient is thought to be a signi cant in uence impacting species composition and structure (Rawat 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diverse topography and elevation range in the mountainous forest ecosystem had a signi cant impact on the environmental microclimate (Qanbari, and Jamali, 2015), vegetation cover, and soil properties over a relatively short distance, frequently with sudden transitions (ecotone) in the vegetation sequences. The most important environmental elements that may contribute to the decline in growth and developmental features along an altitudinal gradient include temperature, light intensity, soil moisture, and fertility status in the alpine ecosystem (Kumar et al 2022b). Due to changes in abiotic variables such as climate, soil, and temperature as well as the altitudinal gradient, especially in undisturbed mountain ecosystems, the altitudinal gradient is thought to be a signi cant in uence impacting species composition and structure (Rawat 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly,Rajwar et al (1999) suggested the climatic and biotic stress in uence the regeneration potential of species and pointed out that the proportionate conversion of seedlings into sapling stage affected by biotic disturbances and competition for space and nutrients. Furthermore,Kumar et al (2022b) revealed that the Juniperus macropoda tree's growth and development qualities, such as crown height, crown breadth, crown length, and stand characteristics, were highest at lower elevation ranges and considerably decreased along the gradient of elevation. Fraxinus xanthoxyloides, as an excellent source of fuelwood, timber, and fodder, another potential explanation for the reduced conversion rate of seedlings into saplings could be the trampling and grazing by both domesticated and wild animals.…”
mentioning
confidence: 99%